Komparasi penerapan konsep green meeting pada penyediaan venue mice di centara grand beach resort samui thailand dan meliá bali indonesia - Sarasswati, Ni Luh Putu; Suarka, Fanny Maharani; Aryanti, Ni Nyoman Sri (Jurnal Kepariwisataan dan Hospitalitas, 2019)
The aim of this research is to find the implementation of Green Meeting concept on the provision of MICE Venue at Centara Grand Beach Resort Samui Thailand and Meliá Bali Indonesia and their differences in its implementation. The variable that used is Green Meeting concept with 5 indicators. That 5 indicators are management, accessibility and social inclusion, catering and service, water and energy efficiency, and waste management. Data obtained through observation, interview, and documentation. The collected data analyzed by using a descriptive-comparative method that approaches by a qualitative method and using Gutman Scale for the measurement. The result shows that the two of the hotel have been implemented Green Meeting concept. Percentages of each hotel are 91.67% for Centara Grand Beach Resort Samui and 79.17% for Meliá Bali. The result also shows that the lowest indicator implementation in two of the hotel is Water and Energy Efficiency Indicator.